Daylight Performance of an Office Building - Vishnu Priya P.; Gnana Priya M.; Mahesh E.; Naga Sai K.; Fareez D.; Navya Chandrika T. (E3S Web of Conferences)
Daylighting plays an important role to enhance the comfort levels for the occupants in the building and also to reduce the usage of artificial lighting during daytime conditions. Excess daylighting of the building increases sun lighting inside the building. Daylighting depends on number of openings provided in each direction of the building and also on wall window ratios. The present study is done for an office building for different orientations with different WWR such as 20%, 25% and 30%. In this study daylight illuminance and day light factor analysis is carried by using daylight simulation in Design Builder. Analysis is done for 12 models. By comparing the analysis, it has been observed that WWR of 25% for all orientation has daylight illuminance value with in desirable ranges when compared to 20% and 30%.